Functional Characterization of Target of Rapamycin Signaling in Verticillium dahliae - Li, Linxuan; Zhu, Tingting; Song, Yun; Luo, Xiumei; Feng, Li; Zhuo, Fengping; Li, Fuguang; Ren, Maozhi (Frontiers in Microbiology, 2019)
More than 200 plants have been suffering from Verticillium wilt caused by Verticillium dahliae (V. dahliae) across the world. The target of rapamycin (TOR) is a lethal gene and controls cell growth and development in various eukaryotes, but little is known about TOR signaling in V. dahliae. Here, we found that V. dahliae strain is hypersensitive to rapamycin in the presence of rapamycin binding protein VdFKBP12 while the deletion mutant △vdfkbp12 is insensitive to rapamycin. Heterologous expressing VdFKBP12 in Arabidopsis conferred rapamycin sensitivity, indicating that VdFKBP12 can bridge the interaction between rapamycin and TOR across species. The key across species of TOR complex 1 (TORC1) and TORC2 have been identified in V. dahliae, suggesting that TOR signaling pathway is evolutionarily conserved in eukaryotic species. Furthermore, the RNA-Seq analysis showed that ribosomal biogenesis, RNA polymerase II transcription factors and many metabolic processes were significantly suppressed in rapamycin treated cells of V. dahliae. Importantly, transcript levels of genes associated with cell wall degrading enzymes (CWEDs) were dramatically down-regulated in TOR-inhibited cells. Further infection assay showed that the pathogenicity of V. dahliae and occurrence of Verticillium wilt can be blocked in the presence of rapamycin. These observations suggested that VdTOR is a key target of V. dahliae for controlling and preventing Verticillium wilt in plants.